Greenhouse gas emission estimate in sugarcane irrigation in Brazil: Is it possible to reduce it, and still increase crop yield? - Cardozo, Nilceu Piffer; Bordonal, Ricardo De Oliveira [UNESP]; La Scala, Newton [UNESP] (Elsevier, 2016)
Irrigation increases sugarcane yield, especially in areas under restricted rainfall conditions. However, few studies have been carried out on the environmental impacts of this activity, mainly regarding greenhouse gas (GHG) emissions. Therefore, the aim of this study was to estimate the environmental impacts of sugarcane irrigation, contemplating GHG emissions at different production scenarios. For that, biomass production was simulated under rainfed conditions and different irrigation systems, comparing six Brazilian regions (Ribeirão Preto - SP; Araçatuba - SP; Paracatu - MG; Itumbiara - GO; Paranaíba - MS; and Petrolina - PE). After gathered, GHG emission estimates of each scenario were confronted with sugarcane production data. The results were expressed in carbon (C) footprint (kg CO2eq t-1). For all evaluated regions, irrigation intensifies and encumbers environmentally the agricultural practices by increasing GHG emissions (∼7447.0 kg CO2eq ha-1 yr-1) compared with rainfed condition (∼2154.6 kg CO2eq ha-1 yr-1). Irrigation systems require a large amount of electric power, diesel and other inputs such as synthetic nitrogen fertilizers. Surprisingly, this situation can change substantially if C footprint is considered. We observed that irrigated areas had a decrease C footprint of up to 59% (33.0 kg CO2eq t-1) against rainfed ones, as observed in Petrolina scenario. In other regions, C footprint reductions ranged from 23% (7.1 kg CO2eq t-1) in Ribeirão Preto to 37% (13.9 kg CO2eq t-1) in Paracatu. Thus, irrigated agriculture impact could be explored in terms of C footprint, which depends on regional biomass production as well as irrigation system efficiency towards a better water use.
Keywords: Carbon footprint; Climate change; Greenhouse gas inventory; Modeling; Saccharum officinarum; Sustainable production